Overexpression of TIGIT in NK and T Cells Contributes to Tumor Immune Escape in Myelodysplastic Syndromes - Meng, Fanqiao; Li, Lijuan; Lu, Fengzhu; Yue, Jing; Liu, Zhaoyun; Zhang, Wei; Fu, Rong (Frontiers in Oncology, 2020)
Objective: Targeting immune checkpoints, such as PD-1, represents a promising approach for cancer immunotherapy, achieving long-term disease remission rates in numerous types of cancer. T cell immunoglobulin and ITIM domain (TIGIT) is a checkpoint receptor associated with the antitumor roles of NK and T cells. Notably, the blockade of TIGIT has been revealed as a potential promising approach in cancer immunotherapy. However, the therapeutic potential of blocking TIGIT in myelodysplastic syndrome (MDS) remains unclear and further research is required to reveal their role. Methods: Fresh peripheral blood (PB) and bone marrow (BM) were obtained from patients with MDS and healthy donors (HDs) at the Tianjin Medical University General Hospital between January 21 2018 and March 22 2019.The present study investigated the expression levels of TIGIT on NK and T cells using flow cytometry (FCM) and PCR. In addition, other checkpoint receptors, such as CD226 and PD-1, were also investigated. To determine the mechanisms of antitumor immunity, the functions of NK and T cells expressing TIGIT were determined. Results: TIGIT was found to be highly expressed on NK and T cells of the PB, where it was involved in disease progression and the immune escape of MDS. The high expression levels of TIGIT were associated with decreased NK and T cell function, and significantly lower secretions of activation factors, such as CD107a, IFN-γ and TNF-α. Notably, blocking TIGIT enhanced the antitumor effects of NK and T cells. Conclusions: In conclusion, the results of the present study suggested that targeting TIGIT alone or in combination with PD-1 may be a promising anticancer therapeutic strategy in MDS.